Evaluation of the role of whiB6 and kdpDE in the dominant multidrug-resistant clone Mycobacterium tuberculosis B0/W148 - Isabelle Bonnet; Mickael Orgeur; Florence Brossier; Fadel Sayes; Wafa Frigui; Jan Madacki; Hugo Varet; Aurélie Chauffour; Alexandra Aubry; Nicolas Veziris; Wladimir Sougakoff; Roland Brosch; et al. (Microbiology Spectrum)
ABSTRACT Multidrug-resistant (MDR) strains of Mycobacterium tuberculosis represent an obstacle to eradicating tuberculosis (TB) due to the low treatment success rate of MDR TB. Among them, the MDR B0/W148 clone has recently evolved from the M. tuberculosis Beijing lineage 2 and is widely disseminated in Russia and Europe. To get more insights into the genetic factors underlying the evolutionary success of the MDR M. tuberculosis B0/W148 clone in addition to environmental and patient-related features, we focused on two mutations specific to this clone that are found in the transcriptional regulators WhiB6 and KdpDE and investigated in a H37Rv strain background the transcriptional profile associated with these mutations and their impact on the in vitro and in vivo growth characteristics. Through the construction and use of H37Rv∆whiB6, H37Rv∆kdpDE, and complemented strains, neither mutation impaired the in vitro growth of M. tuberculosis in standard mycobacterial growth media. The mutation T51P in whiB6 prevented the upregulation of 9 genes in the esx-1 core region and 44 genes elsewhere in the genome, while the deletion of two nucleotides in kdpD leads to a fusion protein of KdpD with KdpE that inhibits the transcriptional activity of KdpE. Neither mutation led to hypervirulence in a mouse infection model. These results point to the role of other MDR B0/W148 specific mutations in the wide geographic diffusion of this clone and/or put in question a hypothesized hypervirulence as a driving factor for this large dissemination.IMPORTANCEHuman tuberculosis (TB), caused by the bacterium Mycobacterium tuberculosis, remains a global public health issue estimated to have been responsible for 1.25 million deaths in 2023. Multidrug-resistant (MDR) strains of M. tuberculosis, resistant to rifampicin and isoniazid, lead to lower treatment success. Among them, the MDR B0/W148 clone has widely disseminated in Russia and Europe. To get more insights into the genetic factors underlying the evolutionary success of this clone, we investigated two strain-specific mutations found in the transcriptional regulators WhiB6 and KdpDE. By constructing and analyzing laboratory M. tuberculosis strains carrying these specific mutations, we found numerous changes in their transcriptional profiles, whereas we observed only a little impact of these mutations on the virulence of M. tuberculosis in a mouse infection model. Our study provides new insights into the transcriptional landscape of the selected MDR strains, although no direct connection to virulence could be established.